ASSISTANCE IN MAKING WORKING AGREEMENTS TYPE: FIXED TIME EMPLOYMENT AGREEMENT AND FIXED-TER M EMPLOYMENT AGREEMENT AT PT. GLOBAL YUPITER INDONESIA - Shenti Agustini; Vania Virginia (ConCEPt - Conference on Community Engagement Project, 2022)
As one of the implementations of the Work Practice program, the author chose to assist PT. Global Yupiter Indonesia in creating or designing a Work Agreement or it can also be called a Work Contract by following the directions of PT. Global Yupiter Indonesia, but still pay attention to the applicable laws. This is necessary to minimize the risk of problems between PT. Global Yupiter Indonesia as the employer and its workers. Considering that in the world of employment, there must be several rights and obligations that must be fulfilled by the parties in the employment relationship, namely the role of the employer and worker.The type of research that the author uses is normative-empirical / applied legal research using primary data sources obtained from the field and interviews with PT. Global Yupiter Indonesia. For the purpose of achieving within a period of 3 (three) months, the author adjusts the form of the Work Agreement according to the requests, circumstances, and also needs of PT. Global Yupiter Indonesia by staying guided by the applicable Labor Act. In making, the author divides the process into 3 (three) stages, namely the preparation stage as a prefix, then implementation, and then the assessment of reporting. The exterior of the Practical Work program that the author carries out is in the form of a draft of a Fixed Time Employment Agreement (PKWT) and a Fixed-Term Employment Agreement (PKWTT).